The Midwife - Nicole Dickson (African Journal of Gender and Religion (AJGR))
This article explores the metaphor of midwife as a statement of position for supporting pastoral and self-care during Covid-19 times. It weaves collabora-tive threads of narrative therapy, feminism, and pastoral theology to explore meaning-making, the importance of stories, metaphors, and 'voice' using the familiar language of pregnancy, namely 'expectancy, labour pains, and 'birth'. It seeks to offer a compassionate space for bearing witness to the effects of the pandemic on therapists and the people we encounter.